UJI AKTIVITAS FAGOSITOSIS MAKROFAG EKSTRAK TANAMAN GEDI Abelmoschus Manihot (L) SEBAGAI IMUNOMODULATOR - Ciptanti Prakarsa; Widdhi Bodhi; Olvie Syenni Datu (PHARMACON, 2024)
Gedi plant (Abelmoschus manihot L.) is one of the plants that contain flavonoids which have not been made into preparations for medicinal purposes. The purpose of this study was to determine the effectiveness of gedi plant extract as an immunomodulator. By looking at the activity and capacity of mouse macrophages (Rattus norvegicus) with Staphylococcus auereus bacteria in vitro. The results showed that gedi leaf extract had a significant effect on the activity and capacity of macrophages P(<0.05) which stated that gedi leaf extract had effectiveness as an immunostimulant. At a concentration of gedi plant extract of 1000 ppm, the activity and phagocytosis capacity showed the highest values, namely 87.66% and 4.23.